Shared responsibility: the who, what and how. (2nd October 2017) - Lukasiewicz, Anna; Dovers, Stephen; Eburn, Michael
ABSTRACT: As natural disasters increase around the world and stretch the capacities of emergency services, national governments and international institutions have stressed the importance of shared responsibility; the idea that all actors within a society have some obligations in disaster management and must work collectively to reduce disaster risk. However, the exact balance between individual and government responsibility is not yet established and continually contested, especially after major events. In Australia, the National Strategy for Disaster Resilience (NSDR) is the overarching policy framework for disaster risk management and aims to create resilient communities through an emphasis on shared responsibility and empowerment. Through a literature review and document analysis of the NSDR and associated policy documents, we clarify, organise and operationalise the necessarily general policy goal of shared responsibility. We first analyse how the NSDR conceptualises communities to discover which community actors are mentioned. We then identify the responsibilities it prescribes or implies for these different actors and consider the types of policy instruments that are relevant to disaster risk management. Our analysis reveals a tension between the NSDR's placement of government at the centre of disaster risk management, and its other, less well-explained emphasis on community empowerment.